Pengembangan Modul Pembelajaran Desain Kemasan Dengan Menggunakan Sofware Coreldraw X4 Pada Mata Kuliah Desain Grafis - Tito (Jurnal Sains Informatika Terapan, 2022)
Research begins with the development of computer technology in particular has been used as a medium of learning Packaging Design Using CorelDraw programs in various fields of one form of education in the field of Fine Arts Visual Communication Design Study Program. This requires education student majoring in Fine Arts Communication Design Visual Languages and Arts Faculty, State University of Padang to be able to utilize these technologies in the field of Packaging Design, as computer technology has become a necessity for people, especially in the field of product design food packaging and logo design, research this development method, which is to design and make a product logo and packaging design as well as media advertising, then tested the feasibility of the students of Communication Design Visual Arts UNP Padang. Design and manufacture of this learning module using the CorelDraw X4 software. Data collection techniques in this study using a questionnaire given to faculty and student responses to the questionnaire module packaging design. Questionnaires were made regarding the form, content, motivation and practical learning modules, questionnaire data were analyzed using the SPSS formula. From these results, the learning module packaging design in graphic design courses is valid.